Karakteristik Fitokimia Yoghurt Probiotik dengan Penambahan Rumput Laut Coklat (Sargassum sp.) - Kusumawati, Estri; Andyarini, Esti Novi; Kumalasari, Mei Lina Fitri; Marisa, Marisa; Sari, Ines Puspita (Persatuan Dosen Kesehatan Masyarakat, 2025)
Obesity was one of the public health challenges that continued to increase globally, including in Indonesia. Innovative efforts in the development of functional foods were required to support the prevention and management of obesity, one of which was through probiotic yoghurt products. Sargassum sp., a type of brown seaweed rich in fiber and bioactive compounds such as fucoidan and fucoxanthin, had potential as an additive in yoghurt. This study aimed to characterize the physicochemical properties of yoghurt enriched with Sargassum sp., including fat content, protein content, and pH. The yoghurt was formulated with varying concentrations of Sargassum sp. (0%, 5%, 10%, and 15%) and analyzed using standard laboratory methods. The results showed that the addition of Sargassum sp. significantly increased the fat and protein content of the yoghurt, but did not provide a significant difference in pH value. These findings indicated that Sargassum sp. had potential to be used as a plant-based fortificant in the development of functional yoghurt with high nutritional value.